1999
DOI: 10.1073/pnas.96.11.6478
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inactivation of the nucleus basalis magnocellularis induces disruption of cortical acetylcholine release and acquisition, but not retrieval, of aversive memories

Abstract: The basal forebrain complex, which includes the nucleus basalis magnocellularis (NBM), provides widespread cholinergic and ␥-aminobutyric acid-containing projections throughout the brain, including the insular and pyriform cortices. A number of studies have implicated the cholinergic neurons in the mediation of learning and memory processes. However, the role of basal forebrain activity in information retrieval mechanisms is less known. The aim of the present study is to evaluate the effects of reversible inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 35 publications
6
50
0
1
Order By: Relevance
“…Initiated by the pioneering work of MacIntosh and Oboring (1955), which demonstrated that ACh controls the neuronal excitability, the interest in the function of the cholinergic system greatly increased with the characterization of cholinergic antagonists as impairment agents of cognitive abilities (Deutsch, 1971;Drachman, 1977) and with the postmortem identification of reduced cholinergic markers in the brain of Alzheimer's disease patients (Bowen et al, 1976;Perry et al, 1978). The cholinergic drive controls a large variety of cognitive processes, such as attention (Hasselmo and Sarter, 2011), learning (Fine et al, 1997;Miranda and Bermú dez-Rattoni, 1999), and memory (Hasselmo and Bower, 1992;Gil-Bea et al, 2010) by boosting the signal-to-noise ratio (Sillito and Kemp, 1983) in various cortical and subcortical nuclei entrained within a complex neuronal network (Everitt and Robbins, 1997). The mutually interacting PFC and hippocampus (Hipp) represent the core of this network involved in cognitive processing (GoldmanRakic, 1995;Thierry et al, 2000;Warburton and Brown, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Initiated by the pioneering work of MacIntosh and Oboring (1955), which demonstrated that ACh controls the neuronal excitability, the interest in the function of the cholinergic system greatly increased with the characterization of cholinergic antagonists as impairment agents of cognitive abilities (Deutsch, 1971;Drachman, 1977) and with the postmortem identification of reduced cholinergic markers in the brain of Alzheimer's disease patients (Bowen et al, 1976;Perry et al, 1978). The cholinergic drive controls a large variety of cognitive processes, such as attention (Hasselmo and Sarter, 2011), learning (Fine et al, 1997;Miranda and Bermú dez-Rattoni, 1999), and memory (Hasselmo and Bower, 1992;Gil-Bea et al, 2010) by boosting the signal-to-noise ratio (Sillito and Kemp, 1983) in various cortical and subcortical nuclei entrained within a complex neuronal network (Everitt and Robbins, 1997). The mutually interacting PFC and hippocampus (Hipp) represent the core of this network involved in cognitive processing (GoldmanRakic, 1995;Thierry et al, 2000;Warburton and Brown, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the structures involved in the initial phases of taste memory formation are the gustatory neocortex and amygdala (8). Thus, damage to either the gustatory insular cortex (IC) or amygdala in adult rats leads to impaired acquisition of CTA (6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17). However, the functional roles of IC and amygdala seem to be different during the phases of taste memory formation.…”
mentioning
confidence: 99%
“…CTA has unique properties; it is established after a single trial, permits long delays between stimuli presentation, and lasts for very long periods of time, even weeks. This feature makes it possible to separate the acquisition process into phases-CS presentation and US presentation-which can be studied independently under different experimental treatments (6).…”
mentioning
confidence: 99%
“…Reduction in the number of mAChR following ODRL Several behavioral studies have suggested a role for ACh in the learning of a new task, but not in exercising the same task after acquisition (Aigner et al 1991;Naor and Dudai 1996;Orsetti et al 1996;Miranda and Bermudez-Rattoni 1999).…”
Section: Discussionmentioning
confidence: 99%